Using a New Phenomenon of Electronic Oscillations Near the Positive Electrode to Generate Powerful Microwave Radiation - Karapetyan, G. G.
A novel microwaves generator scheme is introduced, where electrons perform oscillations within the electric field of a positively charged electrode. This phenomenon is based on a recently developed theory of the interaction of electrons with electric fields, which predicts the presence of a repulsive force acting on an electron near strongly positively charged bodies. Along with the usual attractive force acting at a distance, this newly discovered repulsive force causes specific oscillations of electrons in the vicinity of a positively charged electrode, leading to the generation of electromagnetic radiation. The proposed generator represents a new variant of a vircator, wherein a virtual cathode is formed in front of, rather than behind, a positively charged anode.
Keywords: Physics